Análisis comparativo de la investigación rusa y extranjera sobre la migración docente. / Comparative analysis of Russian and foreign research on teacher migration. - Dmitry Kataev; Anastasia Zemlyanskaya (Universidad de La Habana, 2022)
This article analyses Russian and foreign academic research in the field of teacher migration. The study aims to determine the volume of research on the given subject area. In the article, we have used a comparative analysis of sources, as well as such methods as comparative and structural-functional analysis, and statistical means. The objectives were to study the concept of migration, to identify positive and negative aspects of labor migration, to examine the meaning of the terms educational and intellectual migration, to identify the problems faced by teachers when moving to other countries, based on the works of foreign authors. The teachers' experience in such countries as the USA, Belgium, and Norway was analyzed for this purpose. The main results of the study confirm the relevance of the article's topic. We came to the conclusion that the narrow focus "migration of teachers" is barely studied and requires additional research to identify the causes and factors in teacher professional activities. / RESUMEN Este artículo analiza la investigación académica rusa y extranjera en el campo de la migración docente. El estudio tiene como objetivo determinar el volumen de investigación sobre el área temática dada. En el artículo, hemos utilizado un análisis comparativo de fuentes, así como métodos tales como análisis comparativo y estructural-funcional, y medios estadísticos. Los objetivos fueron estudiar el concepto de migración, identificar aspectos positivos y negativos de la migración laboral, examinar el significado de los términos de migración educativa e intelectual, identificar los problemas que enfrentan los docentes al trasladarse a otros países, a partir de las obras de autores extranjeros. Para ello se analizó la experiencia de los docentes en países como Estados Unidos, Bélgica y Noruega. Los principales resultados del estudio confirman la relevancia del tema del artículo. Llegamos a la conclusión de que el enfoque estrecho "migración de maestros" apenas se estudia y requiere de investigación adicional para identificar las causas y los factores en las actividades profesionales de los maestros.